The ethical paradox in Islamic cooperatives: A lesson learned from scandalous fraud cases in Indonesia's Baitul Maal Wat Tamwil - Dian Kartika Rahajeng (Cogent Business & Management, 2022)
This paper examines the value interplay and governance challenges among cooperatives, particularly operating in an extreme environment such as Indonesia's BMTs (Islamic cooperatives). BMTs act as a "bridge" for small and medium enterprises to gain financial support unobtainable from more formal financial institutions. BMTs have experienced unprecedented growth in Indonesia. Recently, there has been an alarming increase in the instances and magnitude of fraud in BMTs. This paper is built on micro-level evidence showing how value creation and disruption lead to fraud in cooperatives. The author focuses on a specific value interplay process to understand how fraud incidents disrupt internalised values and affect organisational governance. The findings indicate the challenges of the overlapping values in cooperatives in extreme organisational settings and the need for better alignment between micro and macro values to minimise fraud.
Keywords: 650; Indonesia; Cooperative governance; extreme environment; non-traditional organisations; value creation; value disruption